Hypoglycemia in a Pediatric Emergency Department: Single-Center Experience on 402 Children. Issue 1 (3rd December 2020) - Papini, Laura; Piga, Simone; Dionisi-Vici, Carlo; Parisi, Pasquale; Ciofi degli Atti, Marta Luisa; Marcias, Michela; Garrone, Stefano; Scialanga, Barbara; Taurisano, Roberta; Reale, Antonino; Villa, Maria Pia; Raucci, Umberto
Abstract : Objectives: This study aimed to establish the rate, etiology, and short-term outcome of hypoglycemia in infants and children accessing an emergency department of a tertiary care pediatric hospital. Methods: The study was retrospectively conducted on the clinical records of children with hypoglycemia aged 15 days to 17 years who were admitted consecutively to the emergency department during a 6-year period for various clinical conditions. Hypoglycemia was defined as a venous plasma glucose level lower than 45 mg/dL. Results: Hypoglycemia was detected in 402 patients (female-to-male ratio, 1.26; mean age, 2.6 ± 1.8 years), with a rate of 0.99 per 1000 children. Plasma glucose levels ranged from 3 to 45 (mean, 37.48 ± 7.44) mg/dL. Hypoglycemia was associated with gastroenteritis or other infectious diseases causing protracted fasting in 86.32% of cases, whereas hypoglycemia related to a different etiology (HDE) was observed in 13.68% of hypoglycemic children. Most HDE patients had a final diagnosis of ketotic hypoglycemia, whereas metabolic defects were a rare (1.49%) but nonnegligible etiologic cause. A severe triage code was more frequent in the HDE group ( P < 0.001). Factors significantly and independently associated with HDE were impaired level of consciousness, assessed with the AVPU scale (A, alert; V, responding to verbal; P, responding to pain; U, unresponsive; adjusted odds ratio, 2.50; P = 0.025) and clinical onset within 12 hours (adjusted odds ratio, 3.98; P < 0.001). Conclusions: In a nonnegligible number of critically ill children, hypoglycemia can be detected. In a minority of cases, hypoglycemia was due to metabolic disorders that should be suspected on the basis of the severity of hypoglycemia, and the recent onset and the presence of neuroglycopenic symptoms.